Dual-supramolecular contacts induce extreme Hofmann framework distortion and multi-stepped spin-crossover. Issue 4 (13th January 2021) - Ahmed, Manan; Brand, Helen E. A.; Peterson, Vanessa K.; Clegg, Jack K.; Kepert, Cameron J.; Price, Jason R.; Powell, Benjamin J.; Neville, Suzanne M.
Abstract : A ligand with dual-supramolecular contact character has been exploited to induce extreme Hofmann framework distortion and a resultant multi-stepped spin-crossover transition behaviour with a mismatch between structural and spin-state periodicity. Abstract : An extended nitro-functionalised 1, 2, 4-triazole ligand has been used to induce considerable lattice distortion in a 2-D Hofmann framework material via competing supramolecular interactions. Single crystal X-ray diffraction analyses on [Fe3 (N-cintrz)6 (Pd(CN)4 )3 ]·6H2 O (N-cintrz: ( E )-3-(2-nitrophenyl)acrylaldehyde) reveal a substantial deviation from a regular Hofmann structure, in particular as the intra- and inter-layer contacts are dominated by hydrogen-bonding interactions rather than the typical π-stacking arrays. Also, the 2-D Hofmann layers show an assortment of ligand conformations and local Fe II coordination environments driven by the optimisation of competing supramolecular contacts. Temperature-dependent magnetic susceptibility measurements reveal a two-step spin crossover (SCO) transition. Variable temperature structural analyses show that the two crystallographically distinct Fe II centres, which are arranged in stripes (2 : 1 ratio) within each Hofmann layer, undergo a cooperative HS ↔ HS/LS ↔ LS (HS = high spin, LS = low spin) transition without periodic spin-state ordering. The mismatch between crystallographic (2 : 1) and spin-state (1 : 1) periodicity at the HS : LS step provides key insight into the competition (frustration) between elastic interactions and crystallographically driven order.